Perception and Satisfaction with the Use of Birth Plan among Postpartum Women in a Nigerian Tertiary Hospital (2013)
Background: The role of choice in child birth is of utmost importance because of women’s need of having control over their birth process, which makes them to be satisfied with the process of child birth. The purpose of the birth pian is to act as a communication tool, to encourage women to make informed choices, to draft a realistic pian of care during labour, and to achieve greater satisfaction from the birth experience. Satisfaction with such a life changing event can be the basis for a positive beginning to early mother/baby interaction and a solid foundation for long term family health. Methods: The study was carried out among women who had at least one child in the postnatal ward and infant welfare clinic of the University College Hospital, Ibadan. A stratified random sampling technique was used in selecting 200 postpartum women from the hospital. A structured questionnaire was administered and analysed using statistical package for social Sciences version 15 (SPSS 15). Results: Majority (90%) of the respondents indicated that being involved with decisions about birth makes them to be satisfied with birth process. The study also revealed that almost all (97%) of the respondents were aware of birth-plan while 72% supported the fact that birth plan help improve communication with health practitioners. Most of the women have a high perception that introduction and use of birth-plan in their care will help enhance childbirth experience and satisfaction. There was a significant association between utilization of birth plan and satisfaction with childbirth process (p=0.015). Conclusion: The gradual shift of maternity care from a paternalistic medical model to a more humanistic approach will encourage active client participation and partnership in care. This will also lead to the rights of women to information and informed choices being advocated. Satisfaction in childbirth is an important indicator of quality of matenity care given today and continuous use of skilled birth attendants.